2003
DOI: 10.1007/s00227-003-1072-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical clam dredging in Venice lagoon: ecosystem effects evaluated with a trophic mass-balance model

Abstract: Harvesting of the invasive Manila clam, Tapes philippinarum, is the main exploitative activity in the Venice lagoon, but the mechanical dredges used in this free-access regime produce a considerable disturbance of the lagoon ecosystem. An ecosystem approach to study the complex effects of clam harvesting was implemented using a trophic mass-balance model. The trophic relations in the ecosystem were quantified with a mixed trophic impact analysis and further evaluated by considering different explanations for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…From 1998 until 2003, the three investigated areas were almost uncolonized by macrophytes. It was extensively reported that in this period, the disappearance of submerged vegetation was at least partly due to the significant illegal clam fishing [69]. This activity strongly interacted the benthic compartment and contributed to the process of sediment resuspension and erosion, causing a decrease in water transparency and light availability.…”
Section: Discussionmentioning
confidence: 96%
“…From 1998 until 2003, the three investigated areas were almost uncolonized by macrophytes. It was extensively reported that in this period, the disappearance of submerged vegetation was at least partly due to the significant illegal clam fishing [69]. This activity strongly interacted the benthic compartment and contributed to the process of sediment resuspension and erosion, causing a decrease in water transparency and light availability.…”
Section: Discussionmentioning
confidence: 96%
“…Successfully invading thermophilic species are expected to take advantage of increased average temperatures (Dulčić and Grbec, 2000; UNEP -MAP -RAC/SPA, 2008; Dulčić et al, 2010Dulčić et al, , 2011Brotz and Pauly, 2012;Zenetos et al, 2012;Pecarevič et al, 2013) but they also need to either find or make trophic niche space, such as by outcompeting native species (e.g., Pranovi et al, 2003). Meanwhile, some local native species might be negatively affected by higher temperatures, but may be able to exploit new trophic opportunities as a trade-off.…”
Section: Introductionmentioning
confidence: 99%
“…On the fishing management plans, the activities impacting the bottoms have to be carefully assessed to avoid the sediment resuspension and the nest destruction. As an example, in the late 1990s, in the Venice lagoon, the clam harvesting activity with hydraulic and mechanical dredging systems that dug 10-30 cm deep furrows dramatically affected the biological equilibrium and the benthic communities [98,99].…”
Section: Managementmentioning
confidence: 99%